Appropriate and inappropriate vitamin supplementation in children. (2020) - Martini, Lucia; Pecoraro, Luca; Salvottini, Chiara; Piacentini, Giorgio; Atkinson, Richard; Pietrobelli, Angelo
Abstract: The vitamin status of a child depends on many factors and most of the clinical studies do not take into account the different access to adequate nutrition of children coming from different countries and the consequent major differences in micronutrients or vitamin deficits between low-income and high-income countries. Vitamin supplements are included in the general field of dietary supplements. There is a large amount of not always factual material concerning vitamin supplements, and this may sometimes create confusion in clinicians and patients. Inadequate information may lead to the risk of attributing beneficial properties leading to their over-use or misuse in the paediatric field. Vitamin supplementation is indicated in all those conditions in which a vitamin deficiency is found, either because of a reduced intake due to reduced availability of certain foods, restrictive diets or inadequate absorption. The lack of guidelines in these fields may lead paediatricians to an improper use of vitamins, both in terms of excessive use or inadequate use. This is due to the fact that vitamin supplementation is often intended as a therapy of support rather than an essential therapeutic tool able to modify disease prognosis. In fact, various vitamins and their derivatives have therapeutic potential in the prevention and treatment of many diseases, especially in emerging conditions of paediatric age such as type 2 diabetes and the metabolic syndrome. The aim of the present article is to analyse the state of the art and consider new perspectives on the role of vitamin supplements in children.